A Life Under Russian Serfdom - Boris B. Gorshkov (Central European University Press, 2005)
This is a translation of one of very few Russian serfs' memoirs. Savva Purlevskii recollects his life in Russian serfdom and life of his grandparents, parents, and fellow villagers. He describes family and communal life and the serfs' daily interaction with landlords and authorities. Purlevskii came from an initially prosperous family that later became impoverished. Early in his childhood, he lost his father. Purlevskii did not have a chance to gain a formal education. He lived under serfdom ...